Adolescent Trauma and Impact of the COVID-19 Pandemic in the School Context - Kalogeratos, Gerasimos; Anastasopoulou, Eleni; Tsagri, Angeliki; Tseremegklis, Chrysostomos; Tsogka, Danai; Lourida, Konstantina; Drongitis, Anastasios (Technium Social Sciences Journal, 2024)
This study examines the significant effects of the COVID-19 pandemic on adolescent trauma and its subsequent consequences in the school setting. The pandemic has brought about a worldwide health emergency that goes beyond physical health, significantly impacting the mental and emotional well-being of teenagers. This demographic, which is already vulnerable to different types of psychological distress during a crucial period of growth, encountered intensified difficulties as a result of the disruptions caused by the pandemic. The study employs a mixed-method methodology, combining quantitative data from surveys with qualitative insights gathered through interviews and focus groups that include students, teachers, and school counselors. The objective is to evaluate the prevalence of trauma-related concerns among adolescents during the pandemic and investigate how these concerns have become apparent in educational environments. Primary concerns include the consequences of extended school closures, the transition to remote learning, social seclusion, and the broader psychosocial pressures associated with the pandemic. The findings indicate a notable surge in the number of reports concerning anxiety, depression, and other symptoms associated with trauma among adolescents. The interruption of typical school schedules and the lack of a physical school setting have decreased academic involvement and drive. Moreover, the absence of face-to-face social engagement and participation in extracurricular activities has intensified sentiments of isolation and social detachment. The study emphasizes the crucial role of schools in offering assistance and resources to tackle these difficulties. It highlights the necessity of implementing trauma-informed educational strategies and mental health support systems in schools to address the increased emotional and psychological requirements of students. Furthermore, the study identifies successful tactics schools utilize to lessen the consequences of the pandemic, such as incorporating mental health education into the curriculum, offering virtual counseling services, and cultivating a supportive online community.